THE IMPACT OF BRAND IMAGE AND SELF-CONCEPT ON MOBILE PHONE PURCHASE DECISION - I Gede Wiyasa; Arys Prada; Enny Istanti; Achmad Daengs GS (Journal of Managerial Sciences and Studies, 2025)
This research is motivated by the rapid development of technology, which has led to the emergence of various new products, particularly in the mobile phone category, intensifying market competition. Mobile phones have become essential items in daily life, making it increasingly difficult for mobile phone brands to stand out. As a result, companies strive to attract consumers by leveraging product features. The aim of this study is to determine the effect of brand image and self-concept on purchasing decisions. Data was collected using a questionnaire with purposive sampling technique on 89 respondents who use mobile phones. The population consists of male and female students at Universitas 45 Surabaya. The independent variables in this study are brand image, self-concept, and purchase decision. Hypothesis testing using multiple regression analysis shows that both independent variables significantly influence the dependent variable (purchase decision). The R-value of 0.718 indicates a strong relationship, close to 1, and the coefficient of determination (R²) is 0.515.